PENGARUH LIMBAH CAIR NANAS (LCN) TERHADAP PERTUMBUHAN DAN KANDUNGAN LEMAK Chlorella sp - Triana, Leli; Sutanto, Agus (JURNAL LENTERA [PENDIDIKAN PUSAT PENELITIAN LPPM UM METRO], 2016)
The purpose of this study was to determine (1) Analyze the influence of the variation media of pineapple liquid waste  (PLW) to increase the growth of Chlorella sp. (2) Analyze the influece the variation of media to increase the fat of Chlorella sp. (3) To determine Media Concentration of pineapple liquid waste to optimal level  for the growth of Chlorella sp. (4) Determine the optimum concentration of pineapple liquid waste for the highest fat content in Microalgae (Chlorella sp.)  This study uses design experimental method, design of the design used is Variety Complete Randomized Design (CRD) with one control (PLW 0%), and 5 treatments PLW 20%,40%,60%,80% and 100% which each four times repeated. 5 ml Chlorella sp. The early density 8 x104  cell/ml inoculated in 100 ml PLW.   For each culture media were cultivated for 10 days. The calculation Chlorella sp. Conducted which calculated the amount of cell/day as long as cultivation. Meanwhile the calculation of fat content conducted at the end of cultivation. Anlyzed used Multy-Variant.Based on study result and explanation were got conclusion (1) Significant influence of variation media pineapple liquid waste toward the growth and fat content of Chlorella sp. (2) Cell density of Chlorella was highest in pineapple liquid waste media 100% (3) The highest fat content was found in concentratin media 60% pineapple liquid waste.